Transformation of Celestial Imagery in Artistic and Ego-Documentary Texts of Nikolai Gumilev During World War I - A. V. Filatov (Научный диалог, 2024)
This article focuses on the analysis of the motif and imagery complex of the night sky in the poetry, autobiographical prose, and letters of Nikolai Gumilev created during World War I. The aim of the study is to establish genetic connections among texts of various natures, examining how the war influenced the poet’s worldview and the aesthetic-philosophical principles of his work. The materials under investigation include the poem “Sacred Nights Drift and Fade...”, the fourth part of “Notes of a Cavalryman,” as well as frontline letters addressed by the poet to Anna Akhmatova and L. M. Reisner. The novelty of this research lies in the fact that these works were not included by Gumilev in his lifetime publications, thus rarely coming to the attention of scholars and remaining insufficiently studied from a comparative-genetic perspective. It is proposed that these texts share a common biographical foundation, as they reproduce a similar situation of observing the night sky during a military lull. The study concludes that the examined complex possesses an ambivalent semantics within Gumilev’s artistic system, drawing upon both Acmeist and Symbolist interpretations, indicating an evolution in the poet’s views as he distances himself from his previously proclaimed aesthetic-philosophical principles during the war.